2023
DOI: 10.1111/sjop.12967
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Post Critical Incident Seminar on emergency service personnel: The critical incident–related experiences and psychological state

Sanna Korpela,
Hilla Nordquist

Abstract: IntroductionPost Critical Incident Seminar (PCIS) is an intervention originally developed by the Federal Bureau of Investigation (FBI) for supporting law enforcement officers who have faced critical incidents (CIs) at work. In Finland, police forces have arranged modified PCIS regularly since 2012, but the first PCIS for emergency service personnel was organized in 2020. PCIS consists of psychoeducation, peer support, and mental health professional support/Eye Movement Desensitization and Reprocessing (EMDR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Thus, the occupational health service may not cover enough psychologist visits for the paramedics to actually recover. Recent studies [ 31 , 58 , 59 ] conducted in Finland have demonstrated the impacts of attending a Post Critical Incident Seminar (PCIS); a support intervention aimed at emergency service personnel who have encountered critical incidents, such as WPV. The PCIS was originally developed for police officers, and participants are provided psychoeducation, peer support and therapeutic services [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the occupational health service may not cover enough psychologist visits for the paramedics to actually recover. Recent studies [ 31 , 58 , 59 ] conducted in Finland have demonstrated the impacts of attending a Post Critical Incident Seminar (PCIS); a support intervention aimed at emergency service personnel who have encountered critical incidents, such as WPV. The PCIS was originally developed for police officers, and participants are provided psychoeducation, peer support and therapeutic services [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCIS was originally developed for police officers, and participants are provided psychoeducation, peer support and therapeutic services [ 31 ]. Participating in PCIS may decrease symptoms of traumatic stress, depression and anxiety [ 58 ] and help participants improve their coping skills [ 59 ].…”
Section: Discussionmentioning
confidence: 99%